2016
DOI: 10.1371/journal.pone.0150370
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Head Circumference, Brain Volume and Cognition in Children with Prenatal Alcohol Exposure

Abstract: Head circumference is used together with other measures as a proxy for central nervous system damage in the diagnosis of fetal alcohol spectrum disorders, yet the relationship between head circumference and brain volume has not been investigated in this population. The objective of this study is to characterize the relationship between head circumference, brain volume and cognitive performance in a large sample of children with prenatal alcohol exposure (n = 144) and healthy controls (n = 145), aged 5–19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…FASD is a neurodevelopmental disorder that impairs the development of cognition, emotion, and motor abilities in children (Jacobson and Jaconson, 2002;Kalberg et al, 2006;Riley et al, 2011). Several studies have found altered development trajectories of brain structure in children and adolescents with PAE compared to healthy controls (Gautam et al, 2015;Lebel et al, 2008Lebel et al, , 2012Treit et al, 2014Treit et al, , 2016, including in the sensorimotor areas studied here. In our study, FC between the facial sensorimotor region and the right insula showed different agerelated changes in PAE compared to healthy controls: FC increased in controls but not in those with PAE.…”
Section: Altered Sensorimotor Fc Development In Paementioning
confidence: 77%
See 1 more Smart Citation
“…FASD is a neurodevelopmental disorder that impairs the development of cognition, emotion, and motor abilities in children (Jacobson and Jaconson, 2002;Kalberg et al, 2006;Riley et al, 2011). Several studies have found altered development trajectories of brain structure in children and adolescents with PAE compared to healthy controls (Gautam et al, 2015;Lebel et al, 2008Lebel et al, , 2012Treit et al, 2014Treit et al, , 2016, including in the sensorimotor areas studied here. In our study, FC between the facial sensorimotor region and the right insula showed different agerelated changes in PAE compared to healthy controls: FC increased in controls but not in those with PAE.…”
Section: Altered Sensorimotor Fc Development In Paementioning
confidence: 77%
“…All control participants were free of diagnosed developmental disorders and FASD. This sample overlaps with previously published studies of structural brain abnormalities (Paolozza, Treit, Beaulieu, & Reynolds, 2014Treit et al, 2016). Informed consent was obtained from a parent or guardian before scanning.…”
Section: Participantsmentioning
confidence: 99%
“…Head circumference at birth is a marker for brain development throughout gestation14 and predictive of cognition in later life15, especially for more vulnerable children (born low birth weight, premature, or with intrauterine growth restriction)16 and those exposed to alcohol during pregnancy17. It is currently unknown whether in general population terms, head size is associated with varying levels of prenatal alcohol exposure, given the scant epidemiological evidence18192021, and again the potential for residual confounding.…”
mentioning
confidence: 99%
“…A previous study, head circumference correlates with the brain volume and is very much affected by age; hence, head circumference measurement by age can be used to determine the presence of brain volume abnormality. 11 Result of this study showed that seven patients had macrocephaly. Patients with macrocephaly are within 0-24 months old with open anterior fontanel.…”
Section: Discussionmentioning
confidence: 78%